2004
DOI: 10.1364/opex.12.003996
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional bioluminescence tomography with model-based reconstruction

Abstract: A model-based image reconstruction method, bioluminescence tomography (BLT), is described. BLT has the potential to spatially resolve bioluminescence associated with gene expression in vivo, thus, offering a tomographic molecular imaging method. The three-dimensional spatial map of reporter genes is recovered using a diffusion equation model-based, finite element reconstruction algorithm. The imaging method is demonstrated using both numerical simulations and phantom experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 1 publication
1
87
0
Order By: Relevance
“…Recently, Wang et al described the BLT principles and reported the uniqueness of solution dependent on a priori knowledge [14,15]. Partial numerical studies were also reported in the recent literature [16,17]. In the present work, we develop a novel reconstruction algorithm to identify the bioluminescent source distribution from the measured external photon density.…”
Section: Introductionmentioning
confidence: 92%
“…Recently, Wang et al described the BLT principles and reported the uniqueness of solution dependent on a priori knowledge [14,15]. Partial numerical studies were also reported in the recent literature [16,17]. In the present work, we develop a novel reconstruction algorithm to identify the bioluminescent source distribution from the measured external photon density.…”
Section: Introductionmentioning
confidence: 92%
“…BL tomography (BLT) would give the ability to reconstruct cross-sectional slices through the BL site(s) and recover depth and spatial resolution of BL sources and could significantly enhance contrast resolution and quantitative accuracy. However, BLT requires the incorporation of an accurate photon migration model into the reconstruction process to account for light absorption and scatter along any given path of the photons [33,34]. For tomographic imaging capabilities, since the surface radiance strongly depends upon the tissue thickness that the light traverses, a special light source should be available to measure the 3D contours of the surface of the animal.…”
Section: Bl Tomography?mentioning
confidence: 99%
“…These properties will provide more useful correlation to images from other modalities, such as PET. However, the very low BL quantum yield, high scatter and absorption, and significant tissue heterogeneity make in vivo BLT an extremely challenging problem [33,34].…”
Section: Bl Tomography?mentioning
confidence: 99%
“…In addition, optical imaging has several other advantages over the established modalities [17][18][19]: the use of low-energy electromagnetic waves in the nearinfrared range poses no risk of ionizing radiation. Optical imaging can provide spectroscopic information on tissue composition [20,21].…”
Section: Biophotonicsmentioning
confidence: 99%